Talam Cake Ordering System - Zamri, Masturina Balqiz; Othman, Muhaini (Applied Information Technology And Computer Science, 2024)
Talam cake ordering system is a system developed for purchasing talam cakes through online. Zamrich Laris Enterprise specializes in making Kuih Talam, a customary dessert from Malaysia, however for the moment, orders are placed manually using WhatsApp. The firm finds it difficult to record sales and prepare talam orders in a systematic manner; customers also encounter challenges placing orders because of the manual management of WhatsApp. As a result, this approach is highly subjective and uneven. The Talam Cake Ordering System was created with these flaws in mind. This created systems with web-based technology and an organised methodology, all of which were put through rigorous testing. The prototyping methodology was employed in the develeopment of this system. This system is designed with Visual Studio Code, the database is created with Laragon, and Windows 11 is used as the operating system. In order to streamline order placement, minimise manual data entry, and guarantee accuracy in the processing of kuih talam orders for Zamrich Laris Enterprise, it is hoped that this system would be established successfully.